2008
DOI: 10.15288/jsad.2008.69.594
|View full text |Cite
|
Sign up to set email alerts
|

Lapses following Alcohol Treatment: Modeling the Falls From the Wagon

Abstract: Objective-This study investigated transitions between drinking and nondrinking during the first 12 months following treatment and whether transitions in posttreatment drinking are related to alcohol-dependence symptoms.Method-Data from individuals in the outpatient (n = 952) and aftercare (n = 774) arms of Project MATCH (Matching Alcoholism Treatments to Client Heterogeneity) were included in the analyses. Drinking consequences, percentage of drinking days, and drinks per drinking day were used as indicators o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 62 publications
3
40
0
Order By: Relevance
“…For all models, the BIC tended to decrease with each additional latent class and the entropy statistic indicated good classification precision across all models. Given substantive interpretation of the resulting class solutions and prior research (Witkiewitz, 2008; Witkiewitz et al, 2010), we selected the models with three latent classes as the final model within each month of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all models, the BIC tended to decrease with each additional latent class and the entropy statistic indicated good classification precision across all models. Given substantive interpretation of the resulting class solutions and prior research (Witkiewitz, 2008; Witkiewitz et al, 2010), we selected the models with three latent classes as the final model within each month of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The models did differ on the invariance of the τ parameters, as reported in detail below. Based on prior work (Witkiewitz, 2008; Witkiewitz et al, 2010), we hypothesized that the probability of transitioning would be greatest during treatment and in the months following treatment, whereas the rates of transitioning would decrease at the 12-month follow-up when heavy drinking (or non-heavy drinking) states may become more stable. Covariates and treatment group were not considered in the analyses because we were most interested in studying the patterns of stability and change in heavy drinking across time, irrespective of treatment and other covariates.…”
Section: Methodsmentioning
confidence: 99%
“…Five variables were selected as relatively baseline characteristics that have been previously been associated with alcohol relapse: self-efficacy (Witkiewitz, van der Maas, Hufford, & Marlatt, 2007); alcohol dependence severity (Witkiewitz, 2008), marital status (Dawson, Grant, Stinson, Chou, Boji, & Ruan, 2006), treatment history and psychiatric problems (Hufford, Witkiewitz, Shields, Kodva, & Caruso, 2003). Other risk factors were considered based on their availability in the COMBINE data, including readiness to change, social support, drinking network size, and family history of alcohol problems.…”
Section: Methodsmentioning
confidence: 99%
“…Not all models could include identical effects (e.g., no random slopes in GEE, no time effects in OLS). Recent studies have found that mixture models (i.e., representing unmeasured subgroups) and zero-inflated models (i.e., representing nondrinkers as a specific subgroup) improve model fit (Atkins et al, 2013;Witkiewitz, 2008;Witkiewitz et al, 2010); however, these models add computational complexity, require large samples, and are less commonly used in treatment research. Testing the above methods with missing data was, unfortunately, beyond the scope of the present study, and participants with missing data were excluded; therefore, the results should be interpreted as best-case scenarios if missing data are accounted for in an ideal manner.…”
Section: Limitationsmentioning
confidence: 99%